Analisis Gaya Kepemimpinan Transformasional pada Efektivitas Himpunan Mahasiswa Manajemen Periode 2024-2025 - Humaeriyah, Hani; Nuur Alisa , Aldila; Rahmania , Ghaitsa; Raisya Kirana (Lembaga Pengembangan Kinerja Dosen, 2026)
Leadership is an essential element in human life, particularly within a social and organizational context. Transformational leadership plays a vital role in shaping the performance and motivation of organizational members. This research adopts a descriptive qualitative method with a case study approach, enabling a deep and systematic exploration of leadership phenomena. The study aims to analyze the implementation of transformational leadership in the Student Association of the Management Department (HIMA) at Universitas Muhammadiyah Bandung for the 2024–2025 period. Based on the theory proposed by McShane and Von Glinow (2010), the results indicate that transformational leadership has a positive contribution to organizational engagement, motivation, and teamwork among student leaders.